Comparison of an immunochemical assay for plasma fibrinogen and a turbidimetric thrombin clotting technique to discriminate hyperlipidaemic patients from healthy controls. Issue 6 (June 1990) - Knapp, M L; Feher, M D; Carey, H; Mayne, P D
Abstract : Plasma samples from patients attending a lipid clinic (n = 14) and healthy control subjects (n = 21) were assayed for fibrinogen using an immunochemical method (radial immunodiffusion) and a turbidimetric assay based on the thrombin clotting technique. The patients had significantly higher plasma fibrinogen concentrations than controls by both methods, but there was significant overlap between the two groups when fibrinogen was assayed by the thrombin clotting technique; there was almost complete separation of the two groups using the immunochemical assay. This difference in overlap could not be attributed to the presence or absence of fibrinogen degradation products. These findings may have important implications for the choice of method for determining plasma fibrinogen when assays are used for the assessment of cardiovascular risk. It is recommended that plasma fibrinogen should be assayed by both an immuno-chemical and a thrombin clotting method.